Rat Heterotopic Heart Transplantation Model to Investigate Unloading-Induced Myocardial Remodeling - Fu, Xuebin; Segiser, Adrian; Carrel, Thierry P.; Tevaearai Stahel, Hendrik T.; Most, Henriette (Frontiers in Cardiovascular Medicine, 2016)
Unloading of the failing left ventricle in order to achieve myocardial reverse remodeling and improvement of contractile function has been developed as a strategy with the increasing frequency of implantation of left ventricular assist devices (LVADs) in clinical practice. But, reverse remodeling remains an elusive target, with high variability and exact mechanisms still largely unclear. The small animal model of heterotopic heart transplantation in rodents has been widely implemented to study the effects of complete and partial unloading on cardiac failing and non-failing tissue to better understand the structural and molecular changes that underlie myocardial recovery not only of contractile function. We herein review the current knowledge on the effects of volume-unloading the left ventricle via different methods of heterotopic heart transplantation in rats, differentiating between changes that contribute to functional recovery and adverse effects observed in unloaded myocardium. We focus on methodological aspects of heterotopic transplantation, which increase the correlation between the animal model and the setting of the failing unloaded human heart. Last, but not least, we describe the late use of sophisticated techniques to acquire data, such as small animal MRI and catheterization, as well as ways to assess unloaded hearts under “reloaded” conditions. While giving regard to certain limitations, heterotopic rat heart transplantation certainly represents the crucial model to mimic unloading-induced remodeling of the heart and as such the intricacies and challenges deserve highest consideration. Careful translational research will further our knowledge of the reverse remodeling process and how to potentiate its effect in order to achieve recovery of contractile function in more patients.